2015
DOI: 10.2112/si73-084.1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Studies on the Working Mechanism and Bearing Capacity of Bucket Foundations for Offshore Wind Turbines

Abstract: Sun, L.; Huo, Z., and Yan, S., 2015. Design of hydraulic telescopic grouted clamp device and analysis of its closing collision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In recent years, scholars have mainly carried out experimental methods [14][15][16][17][18][19][20][21] and numerical simulations [22][23][24][25][26] to study the bucket foundation with honeycomb bulkheads. In terms of the bearing capacities, Lian et al [18] evaluated the influence of honeycomb bulkheads on the uniaxial bearing capacities by 1g model tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, scholars have mainly carried out experimental methods [14][15][16][17][18][19][20][21] and numerical simulations [22][23][24][25][26] to study the bucket foundation with honeycomb bulkheads. In terms of the bearing capacities, Lian et al [18] evaluated the influence of honeycomb bulkheads on the uniaxial bearing capacities by 1g model tests.…”
Section: Introductionmentioning
confidence: 99%
“…e results showed that honeycomb bulkheads have little influence on the bearing capacities when the load is relatively small, but with increasing load, the effect of the honeycomb bulkheads on the bearing capacities becomes increasingly obvious, resulting in a 6.9% enhancement in the vertical ultimate bearing capacity, 18.3% enhancement in the horizontal bearing capacity, and 16.5% enhancement in the moment bearing capacity. Sun et al [26] compared the vertical capacity and bearing characteristics between the bucket foundations with and without honeycomb bulkheads. e research results showed that the vertical bearing behaviour of the bucket foundation with honeycomb bulkheads is obviously different from that without bulkheads because of the distinctive structure of the former.…”
Section: Introductionmentioning
confidence: 99%